Assessment of the Potential of Sarcandra glabra (Thunb.) Nakai. in Treating Ethanol-Induced Gastric Ulcer in Rats Based on Metabolomics and Network Analysis - Li, Chao; Wen, Rou; Liu, DeWen; Yan, LiPing; Gong, Qianfeng; Yu, Huan (Frontiers in Pharmacology, 2022)
Gastric ulcer (GU) is one of the most commonly diagnosed diseases worldwide, threatening human health and seriously affecting quality of life. Reports have shown that the Chinese herbal medicine Sarcandra glabra (Thunb.) Nakai (SGN) can treat GU. However, its pharmacological effects deserve further validation; in addition, its mechanism of action is unclear. An acute gastric ulcer (AGU) rat model induced by alcohol was used to evaluate the gastroprotective effect of SGN by analysis of the histopathological changes in stomach tissue and related cytokine levels; the potential mechanisms of action of SGN were investigated via serum metabolomics and network pharmacology. Differential metabolites of rat serum were identified by metabolomics and the metabolic pathways of the identified metabolites were enriched via MetaboAnalyst. Furthermore, the critical ingredients and candidate targets of SGN anti-AGU were elucidated. A compound-reaction-enzyme-gene network was established using Cytoscape version 3.8.2 based on integrated analysis of metabolomics and network pharmacology. Finally, molecular docking was applied to verify the acquired key targets. The results showed that SGN exerted a certain gastroprotective effect via multiple pathways and targets. The effects of SGN were mainly caused by the key active ingredients isofraxidin, rosmarinic, and caffeic acid, which regulate hub targets, such as PTGS2, MAPK1, and KDR, which maintain the homeostasis of related metabolites. Signal pathways involved energy metabolism as well as immune and amino acid metabolism. Overall, the multi-omics techniques were proven to be promising tools in illuminating the mechanism of action of SGN in protecting against diseases. This integrated strategy provides a basis for further research and clinical application of SGN.